A presença da colaboração científica em pesquisas brasileiras: um estudo nas áreas de ciência da informação, matemática e odontologia - Hilário, Carla Mara [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Scientific collaboration has been considered an important social activity in the science, which allows the exchange of information, the theoretical and methodological enrichment of those involved, and allows an increase in scientific production and contributes to the visibility of researchers, institutions or countries. In this context, this study attempts to identify the similarities and dissimilarities in relation to the Brazilian scientific collaboration in the areas of Mathematics, Dentistry and Information Science. Specifically, it aims to describe, in a comparative manner, the understanding of Brazilian researchers fellows productivity level 1 at CNPq research to the understanding of scientific collaboration and co-authoring activities in the areas under study. For this, a model questionnaire was sent to researchers fellows of productivity level 1 at CNPq research in the areas of Mathematics, Dentistry and Information Science, with questions on the topic scientific collaboration and co-authorship, the most recurrent type of authorship, main collaborators and coauthors and motivations for teamwork. Was conducted a search for publications in the period 2010-2012 in Currículo Lattes of researchers who answered the questionnaire, and were extracted data on training of researchers, articles, books, book chapters and complete works in event annals published on choice period. It was identified that 78% of participants consider that scientific collaboration and co-authorship are different activities, and the potential and usual number of collaborators in research is between 2 and 3 in Mathematics and Information Science, while the value obtained for area of dentistry was 5 and 6 collaborators. Pointed out that there were differences among areas by identifying main collaborators and co-authors, and the reasons for collaborating vary according to the nature of the research, however, identified a high and close percentages in three areas...

A colaboração científica tem sido considerada uma importante atividade social no meio acadêmico, que permite a troca de informações, o enriquecimento teórico-metodológico dos envolvidos, bem como possibilita um incremento na produção científica e contribui para a visibilidade dos pesquisadores, instituições ou países. Neste contexto, esta pesquisa objetiva identificar as similaridades e dissimilaridades em relação à colaboração científica brasileira nas áreas da Matemática, Odontologia e Ciência da Informação. De forma específica, objetiva descrever e comparar a compreensão dos pesquisadores brasileiros bolsistas de produtividade em pesquisa nível 1 do CNPq quanto ao entendimento das atividades de colaboração científica e coautoria nas áreas em estudo, e analisar a produção científica dos participantes da pesquisa com a finalidade de verificar a coesão entre compreensão, opinião e prática científica dos pesquisadores de cada área. Para tanto, foi enviado um questionário aos bolsistas de produtividade em pesquisa nível 1 do CNPq das áreas da Matemática, Odontologia e Ciência da Informação, com questões sobre a temática colaboração científica e coautoria, o tipo de autoria mais recorrente, principais colaboradores e coautores e as motivações para trabalhar em equipe. Foi realizada uma busca das publicações no período de 2010 a 2012 nos Currículos Lattes dos pesquisadores que responderam ao questionário, e foram extraídas informações sobre a formação, publicações de artigos, livros, capítulos de livros e trabalhos completos em anais de evento. Foi identificado que 78% dos participantes da pesquisa consideram que colaboração científica e coautoria são atividades diferentes, e que o número potencial e usual de colaboradores em pesquisas está entre 2 e 3 nas áreas da Matemática e Ciência da Informação, enquanto o valor obtido para a área da Odontologia foi de...
Keywords: Bibliometria; Ciência da informação; Publicações cientificas; Cooperação intelectual; Co-autoria; Pesquisa matematica; Pesquisa odontologica; Ciência da informação - Pesquisa; Information science